Apparent digestibility of nutrients in fattening pigs (Largewhite x Duroc x Pietrain), fed with taro (Colocasia esculenta (L.) Schott) meal. Technical note - Caicedo, W.; Sánchez, J.; Tapuy, A.; Vargas, J. C.; Samaniego, E.; Valle, S.; Moyano, J.; Pujupat, D. (Cuban Journal of Agricultural Science, 2018)
In order to determine the apparent digestibility of nutrients from taro (Colocasia esculenta (L.) Schott) tubers meal in fattening pigs, three castrated male pigs were used, product of the commercial cross (Largewhite x Duroc x Pietrain), with average live weight of 68 ± 2 kg. The animals were distributed in three treatments: T1 (control diet based on corn and soybean), T2 and T3 (inclusion of 20 and 40 % of taro meal in the diet respectively), according to the Latin square design. The mean comparison was performed with the Duncan test (P≤0.05). There was no significant difference (P> 0.05) in the apparent digestibility coefficients of the dry matter (T1 86.70, T2 88.67, T3 88.77 %), organic matter (T1 90.79, 91.80, 89.90 %) and crude protein (T1 92.46; T2 91.96 %; T3 91.89 %). The rectal digestibility of dry matter, organic matter and crude protein showed high utilization rates, when including 20 and 40% of taro tuberous meal in the diet, which guarantees a food of adequate nutritional characteristics for fattening pigs. Key words: pig feeding, use of nutrients, drying, taro tubers.